Precision Public Health: Is the Concept Endurable to Perdurable - Anjali Modi; Jaydevsinh Vala; Pankaj Bhardwaj; C. D. S. Katoch (NMO Journal)
The present era is characterized by the application of artificial intelligence (AI) in public health. Precision Medicine is an emerging approach for disease prevention and treatment considering individual variability in genes, environment, and lifestyle while precision public health (PPH) amalgamates the concept to individuals and groups of people having similar traits of characteristics. Incorporation of precision medicine approaches into public health strategies, can enhance effectiveness of interventions, maximize the impact of resources, and ultimately improve the health and well-being of communities around the world. The application of PPH is not without concerns of data security, generalisation, “hype,” “bio-markup”, and disparities. The present viewpoint deliberates whether precision public health is actually as novel as highlighted or has it already endured the scientific test and proven beneficence to healthcare prediction, planning and solutions.